(untitled) (Journal of Computational Mathematics, 2021)
This paper deals with the numerical computation and analysis for Caputo fractional differential equations (CFDEs). By combining the p-order boundary value methods (BVMs) and the m-th Lagrange interpolation, a type of extended BVMs for the CFDEs with γ-order (0